KONSEP ITMI’NAN DALAM PERSPEKTIF MULLA SADRA: Analisis Falsafi Terhadap Kegelisahan Eksistensial Zaman Digital - Akhmad Dasuki; Marwa Marwa; Shafa Shafa; Nor Afifah; Nismah Sa’adah (Al-Mufassir: Jurnal Ilmu Alquran, Tafsir dan Studi Islam, 2025)
The advancement of digital technology offers convenience but also introduces profound existential challenges. Anxiety, alienation, and loss of meaning have emerged as common symptoms among individuals constantly exposed to social media and endless streams of information. This article aims to examine the concept of itmi’nan (serenity) in Mulla Sadra’s transcendent philosophy and explore its relevance as a response to existential distress in the digital age. Employing a qualitative method with a philosophical-tafsir approach, the study integrates analysis of QS. Ar-Ra’d: 28 with Sadra’s doctrine of harakah jawhariyyah (substantial motion). The findings reveal that itmi’nan reflects ontological stability achieved when the soul unites with divine reality through spiritual awareness. In a world saturated with digital distractions and artificial self-representations, dhikr functions as an existential therapy that reorients the soul toward its metaphysical center. Sadra’s concept of itmi’nan not only offers inner peace but also opens new directions for soul-based therapy and character education rooted in Islamic spirituality. This study affirms the enduring relevance of classical Islamic philosophy in addressing contemporary existential crises.